Role and mechanism of FOXG1-related epigenetic modifications in cisplatin-induced hair cell damage - Mu, Yu-rong; Zou, Sheng-yu; Li, Ming; Ding, Yan-yan; Huang, Xiang; He, Zu-hong; Kong, Wei-jia (Frontiers in Molecular Neuroscience, 2023)
Cisplatin is widely used in clinical tumor chemotherapy but has severe ototoxic side effects, including tinnitus and hearing damage. This study aimed to determine the molecular mechanism underlying cisplatin-induced ototoxicity. In this study, we used CBA/CaJ mice to establish an ototoxicity model of cisplatin-induced hair cell loss, and our results showed that cisplatin treatment could reduce FOXG1 expression and autophagy levels. Additionally, H3K9me2 levels increased in cochlear hair cells after cisplatin administration. Reduced FOXG1 expression caused decreased microRNA (miRNA) expression and autophagy levels, leading to reactive oxygen species (ROS) accumulation and cochlear hair cell death. Inhibiting miRNA expression decreased the autophagy levels of OC-1 cells and significantly increased cellular ROS levels and the apoptosis ratio in vitro. In vitro, overexpression of FOXG1 and its target miRNAs could rescue the cisplatin-induced decrease in autophagy, thereby reducing apoptosis. BIX01294 is an inhibitor of G9a, the enzyme in charge of H3K9me2, and can reduce hair cell damage and rescue the hearing loss caused by cisplatin in vivo. This study demonstrates that FOXG1-related epigenetics plays a role in cisplatin-induced ototoxicity through the autophagy pathway, providing new ideas and intervention targets for treating ototoxicity.